Enhanced permeability and dielectric constant of NiZn ferrite synthesized in nanocrystalline form by a combustion method - Deka, Sasanka; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2007)
The performance parameters of Ni0.5Zn0.5Fe2O4, synthesized in the nanocrystalline form by an autocombustion method, have been investigated. The sample sintered at 1200 degrees C, with Bi2O3 as additive shows a very high value of initial permeability mu'(i) of > 400 at 1 MHz, with low loss. Similarly, a very high dielectric constant is obtained at lower frequencies. The results show that optimum magnetic and electrical properties can be achieved for the NiZn ferrite nanocrystalline powders synthesized by the present autocombustion method and sintered at a relatively lower temperature of 1200 degrees C when compared with a temperature of 1400 degrees C required for the materials synthesized by the conventional ceramic method.